2013
DOI: 10.2214/ajr.12.10038
|View full text |Cite
|
Sign up to set email alerts
|

Sonography of Greater Trochanteric Pain Syndrome and the Rarity of Primary Bursitis

Abstract: The cause of greater trochanteric pain syndrome is usually some combination of pathology involving the gluteus medius and gluteus minimus tendons as well as the iliotibial band. Bursitis is present in only the minority of patients. These findings have implications for treatment of this common condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
106
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(109 citation statements)
references
References 13 publications
3
106
0
Order By: Relevance
“…61 Trochanteric bursitis, a term well known among clinicians, represents a less common cause of lateral hip pain. Other differentials to consider include external snapping hip and neuropathy of the iliohypogastric or lateral femoral cutaneous nerves.…”
Section: Lateral Hip Painmentioning
confidence: 99%
See 2 more Smart Citations
“…61 Trochanteric bursitis, a term well known among clinicians, represents a less common cause of lateral hip pain. Other differentials to consider include external snapping hip and neuropathy of the iliohypogastric or lateral femoral cutaneous nerves.…”
Section: Lateral Hip Painmentioning
confidence: 99%
“…66 In a retrospective review of the US examinations of 877 patients with greater trochanteric pain syndrome, Long et al found that 50% had tendinosis of the gluteal tendons, 28.5% had a thickened iliotibial band, 20% had trochanteric bursitis, and only 0.5% had gluteal tendon tears. 61 Gluteal tendinosis is diagnosed with US as a thickened tendon with loss of the normal fibrillar tendon architecture with or without superimposed calcifications. 61 Iliotibial band thickening is demonstrated at US examination by fusiform thickening at the level of the greater trochanter.…”
Section: Lateral Hip Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound as a dynamic evaluation modality can visualize external snapping of the hip. In a study of 877 patients with GTPS, Long et al [24] used ultrasound to identify gluteal tendinosis in 50 % of patients, a thickened iliotibial band in 28.5 % of patients, a gluteal tear in 0.5 % of patients, and trochanteric bursitis in 20 % of patients. Incidentally, Long et.…”
Section: Imagingmentioning
confidence: 99%
“…Incidentally, Long et. al concluded that only a minority of patients (20.2 %) were determined to have trochanteric bursitis [24].…”
Section: Imagingmentioning
confidence: 99%